2021
DOI: 10.1159/000517618
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Hypertrophic Cardiomyopathy: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Gender-related differences in phenotypic expression and outcomes have been established in many cardiac conditions; however, the impact of gender in hypertrophic cardiomyopathy (HCM) remains unclear. We conducted a systematic review and meta-analysis to assess the differences in clinical outcomes between female and male HCM patients. <b><i>Methods:</i></b> We searched MEDLINE and EMBASE from inception to October 2020. Included were cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…This study revealed a significant association between female sex and an elevated risk of all-cause mortality compared to male sex in patients with HCM. These findings are consistent with previous meta-analyses that have reported similar outcomes ( 34 , 37 ). Subgroup analysis based on data matching demonstrated that even within the data matching group where heterogeneity was absent, women continued to exhibit a higher risk of all-cause mortality compared to men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed a significant association between female sex and an elevated risk of all-cause mortality compared to male sex in patients with HCM. These findings are consistent with previous meta-analyses that have reported similar outcomes ( 34 , 37 ). Subgroup analysis based on data matching demonstrated that even within the data matching group where heterogeneity was absent, women continued to exhibit a higher risk of all-cause mortality compared to men.…”
Section: Discussionsupporting
confidence: 93%
“…Two recent meta-analyses have investigated sex disparities in HCM. Angkawipa Trongtorsak et al conducted a comprehensive meta-analysis involving 11 studies and 9,427 HCM patients ( 34 ). Their analysis focused on all-cause mortality, HCM-related mortality, and worsening heart failure or hospitalization due to heart failure as primary outcomes of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Although a systematic approach to defining PH etiology was not performed in this retrospective assessment, a thorough chart review did not reveal alternative etiologies of PH. There are data showing worse outcomes in females with HCM ( 16 , 17 ), and data herein clarify that this relationship persists in patients with ApHCM ( 7 ).…”
Section: Discussionsupporting
confidence: 63%
“…Trongtorsak et al . similarly concluded to male predominance in HCM, in their systematic review and meta-analysis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%